Effect of onion extract and hydrogen peroxide on Pseudomonas aeruginosa isolated from urinary tract infection - Hamad, Mohammed Oudah (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Antibacterial activity of the mixture of onion (Allium cepae) extract and hydrogen peroxide was tested on multidrug resistant isolate of P. aeruginosa, obtained from biofilm on medical devices and urinary tract infection (UTI). P. aeruginosa exhibited high resistance rate toward sefitrixone and ciprofloxacin with inhibition zone of resistant of isolates in disc diffusion method was detected at 8 and 13 mm, respectively. While inhibition zone of imipenem for the isolated bacteria was 20 mm. Their decontamination was tested using a mixture of onion leaves aqueous extract 10.7% (w/v) with 1.0% hydrogen peroxide. The mixture showed inhibition of the isolates. It can be concluded that a special antibacterial solution could eradicate multidrug resistant isolate of P. aeruginosa.